Adaptação divergente de Drosophila mercatorum a diferentes ambientes da Mata Atlântica - SANTOS, KAROLINE APARECIDA VIEIRA DOS (2021)
Insects are models for studies on the influence of biotic and abiotic factors on adaptive value components, such as life history and metabolism characters. Among the insects of the order Diptera, Drosophila melanogaster is one of the most studied species. However, analyzes of species and populations in the Neotropics, a region with the greatest diversity of habitats and sources of resources, are scarce. Drosophila mercatorum is a Neotropical species of the repleta group that is abundantly collected in open areas and forests, with and without association with xerophytic vegetation, from several Brazilian biomes. This work aimed to contribute to the understanding of adaptation and population variation of life history characters, such as viability (VI), development time (DT) and dry weight (PS), in addition to the storage of metabolic components, triglycerides (TG), glycogen (GL) and protein (PT), in populations from the Atlantic Forest, with and without association with xerophytic vegetation, from the Southeast and South regions of Brazil. In the first chapter we evaluated and compared these characters from populations of D. mercatorum recently collected and maintained on standard culture medium (banana/agar) with other Neotropical species, D. willistoni, of the subgenus Sophophora, and D. maculifrons and D. ornatifrons subgenus Drosophila, as well as D. mercatorum. The populations of D. mercatorum from the Southeast region showed significantly lower values than those from the South region for all parameters analyzed, with the exception of viability in which there was no difference between the populations of this species. The interspecific comparison did not reflect the phylogenetic relationships, especially for the metabolites. The results suggest that the higher VI (and lower TD) of D. mercatorum and D. willistoni would be related to the ability of these species to explore a greater range of environments, while the lower storage capacity of D. mercatorum metabolites could being a trade-off event is your greatest environmental exploration ability. In the second chapter, we evaluated the effects of different types of diet that differ in rotein:carbohydrate (HPS, EPS and LPS) to verify whether the possible differences between geographically distant populations are changes due to phenotypic plasticity in response to nutritional stress, or whether these differences are due to regional diversification. Our results suggest that, in addition to the dietary effect, a population effect is occurring among individuals in the South and Southeast regions, both in bionomic characters and in metabolic contents in both types of vegetation, and may be a reflection of the environments in which the populations are adapted, together with the stressors of the diets tested on each population.